Integrating Generative Artificial Intelligence in English Language Teaching: An Overview in the IoT Era - Mentesoglu-Karaderi, Idil; Vanci Osam, Ulker; Al-Turjman, Fadi (Springer Nature, 2024)
In the current era of English Language Teaching (ELT) as a foreign/second language, teachers are compelled to review and rethink the nature of their classroom instruction from pedagogical, ideological and technological perspectives. The evolving revolutionary intelligent frameworks in the Internet of Things (IoT) era have assisted significantly in shaping futuristic educational methods/tools which advises teachers to maximize learning opportunities in which learners themselves are expected to optimize their investment in improving target language skills. One way of doing this can be the utilization of an Artificial Intelligence (AI)-driven conversational agent, namely the Digital Human Model, to improve second language (L2) learners’ language skills, which is a highly challenging investment in traditional English as a Foreign Language (EFL) classrooms. This overview summarizes the integration of AI-assisted tools in smart educational contexts generally and in language classrooms specifically, the place of Digital Human Models in language education, samples of research studies conducted to explore how AI-driven technologies may address the problems, and, lastly, some observations regarding the direction of future research in the field. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
International Conference on Artificial Intelligence of Things For Smart Societies, AIoTSS 2024 -- 2024-02-14 through 2024-02-17 -- North Cyprus -- 317189
Keywords: Artificial Intelligence (AI); Digital Human Models (DHMs); English Language Teaching; Internet of Things (IoT)